Exploring the Potential for Fungal Antagonism and Cell Wall Attack by Bacillus subtilis natto - Schönbichler, Anna; Díaz-Moreno, Sara M.; Srivastava, Vaibhav; McKee, Lauren Sara (Frontiers in Microbiology, 2020)
To develop more ecologically sustainable agricultural practices requires that we reduce our reliance on synthetic chemical pesticides for crop protection. This will likely involve optimized biocontrol approaches – the use of beneficial soil microbes to attack potential plant pathogens to protect plants from diseases. Many bacterial species, including strains of Bacillus subtilis, have been explored for their biocontrol properties, as they can control the growth of harmful fungi, often by disrupting the fungal cell wall. A strain that is not often considered for this particular application is Bacillus subtilis natto, primarily known for fermenting soybeans via cell wall degradation in the Japanese probiotic dish “natto”. Because deconstruction of the fungal cell wall – and especially the hydrolysis of fungal chitin – is considered an important biocontrol trait, we were motivated to explore the possible anti-fungal properties of the B. subtilis natto strain. We show that B. subtilis natto can use complex fungal material as a carbon source for growth, and can effectively deconstruct fungal cell walls. We found degradation of fungal cell wall proteins, and showed that growth on a mix of peptides was very strong. We also found that intact fungal cell walls can induce the secretion of chitinases and proteases. Surprisingly, we could show that chitin, the bulk component of the fungal cell wall, does not permit successful growth of the natto strain or induce the secretion of chitinolytic enzymes, although these were produced during exposure to proteins or to complex fungal material. We have further shown that protease secretion is likely a constitutively enabled mechanism for nutrient scavenging by B. subtilis natto, as well as a potent tool for the degradation of fungal cell walls. Overall, our data highlight B. subtilis natto as a promising candidate for biocontrol products, with relevant behaviours that can be optimized by altering growth conditions. Whereas it is common for bacterial biocontrol products to be supplied with chitin or chitosan as a priming polysaccharide, our data indicate that this is not a useful approach with this particular bacterium, which should instead be supplied with either glucose or attenuated fungal material.